Hematological Alternation In Common Carp Fish (Cyprinus Carpio L. 1758) After Exposing to Dursban - Showy, Ban Ghany; Rabee, Adel M. (Iraqi Journal of Science, 2019)
Hematological parameters were used as a biomarker of sub chronic effect of dursban in Cyprinus carpio L. The common carp was exposed sub chronically to the 36, 53,113 Âµg /l concentrations of dursban for six weeks. During the experimental period the results showed a decrease in the red blood cell (RBC), white blood cell (WBC), hemoglobin (Hb), mean corpuscular volume (MCV), and packed cell volume (PCV) in the last two weeks of exposure, while the Mean corpuscular hemoglobin (MCH) and Mean corpuscular hemoglobin concentration (MCHC) were significantly increased. The present study indicates that sub chronic exposures of C.carpio to dursban alter the hematological parameters.